Pola Perilaku Konsumen Muslim Terhadap Fenomena Live Shopping di Tiktok Shop dan Shopee: Perspektif Etika Bisnis Islam - Siti Chasanah (Kartika: Jurnal Studi Keislaman, 2026)
The rapid advancement of digital technology has given rise to the phenomenon of live shopping on platforms like TikTok Shop and Shopee, which has massively reshaped the modern retail landscape. This study aims to analyze the behavioral patterns of Muslim consumers towards the live shopping phenomenon, highlighting the psychological dynamics of Fear of Missing Out (FOMO), impulsive buying behavior, and the marketing tricks employed by live streamers. Utilizing a qualitative descriptive approach through the lens of Islamic Business Ethics, this study evaluates the alignment of these digital practices with Sharia values. The findings reveal that real-time marketing strategies, such as artificial scarcity and time-limit pressure, potentially involve elements of disguised deception (tadlis) and market manipulation (najash). Furthermore, FOMO and impulsive buying triggered by intensive interactions during live shopping sessions drive Muslim consumers into excessive consumption (israf) and squandering (tabzir), which run counter to the principles of maqasid al-shariah, specifically the preservation of wealth (hifz al-mal). This study recommends the enhancement of Sharia-compliant consumption literacy among Muslim consumers and the implementation of standardized digital marketing ethics that foster fairness in the e-commerce sector